Validasi Mini-Book Digital untuk Penguatan Literasi dan Numerasi dalam Pembelajaran Sejarah di SMA - Nofiola, Delifia; Aisiah, Aisiah (Jurusan Sejarah FIS UNP, 2025)
The literacy and numeracy skills of Indonesian students, according to the 2022 Programme for International Student Assessment (PISA), are classified as low. Efforts to improve students' literacy and numeracy skills are potentially feasible through school learning, one of which is through history learning resources in the form of a digital mini-book on the subject of 'Japanese Colonization of Indonesia (1942-1945)'. The purpose of this study was to validate the feasibility of the digital minibook (expert validation) and test its practicality as a learning resource. This study applied a quantitative approach, analyzing data using the mean ( ). The research subjects consisted of material validators, media validators, history teachers, and students, totaling 41 people. The research findings show that; first, the digital mini-book material is classified as feasible, with an average score of 3.46. Second, the quality of the digital mini-book's feasibility, according to the media validator's assessment, is classified as very feasible (an average score of 3.5). Third, the practicality of the digital mini-book is categorized as very practical (average teacher score of 3.67 and average student assessment score of 3.69). Therefore, it can be concluded that the digital mini-book is classified as very feasible and practical for implementation in history learning. Claims regarding the enhancement of student ability (effectiveness) will be verified through subsequent research.